The ligand binding site and transduction mechanism in the inositol-1,4,5-triphosphate receptor. - Mignery, G A (1990)
The inositol-1,4,5-triphosphate (InsP3) receptor consists of a homotetramer of highly conserved 313 kd subunits that contain multiple transmembrane regions in the C-terminal part of the protein. The receptor was expressed in COS cells and its domain structure was studied by mutagenesis. Deletion of the transmembrane regions from the receptor results in the synthesis of a soluble receptor protein that efficiently binds InsP3 but which instead of associating into homotetramers remains monomeric. This result suggests a role for the transmembrane regions in the association of the receptor subunits into tetramers but not in ligand binding. To localize the ligand binding site, further cDNAs encoding truncated receptor proteins were constructed. Assays of InsP3 binding to these truncated InsP3 receptors revealed that sequences in the N-terminal fourth of the InsP3 receptor are sufficient for ligand binding. Accordingly, each subunit of the InsP3 receptor homotetramer contains an independent ligand binding site that is located on the N-terminal ends of each subunit and is separated from the putative channel-forming transmembrane regions by greater than 1400 amino acids. Gel filtration experiments demonstrate a large conformational change of the receptor as a function of ligand binding, suggesting a mechanism by which ligand binding might cause channel opening.